Routing and handoff in the edge mobility architecture. - O'Neill, Alan (Mobile computing and communications review.)
We consider a future IP network architecture in which the core topology is fixed but where the hosts at the edge of the network may be mobile, as is the case in cellular networks. Within this architecture, Mobile-Enhanced Routing (MER) protocols are used to support the prefix-routed requirements of the fixed Internet, along with the movement of IP addresses allocated to mobile nodes. We outline a specific components for the support of such edge mobility (EMA:MER) that offers fixed/mobile IP network convergence, homogeneous IP handoff across heterogeneous access technologies and inter-domain roaming across heterogeneous large-scale IP domains.